2017
DOI: 10.1177/0098628317727645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Higher and Lower Level Writing-to-Learn Assignments on Higher and Lower Level Examination Questions

Abstract: Our study examined whether brief writing-to-learn assignments linked to lower and higher levels in Bloom’s taxonomy affected performance differentially on examination performance in assessing these skill levels. Using a quasi-random design, 91 undergraduate students in an introductory psychology class completed eight lower level and eight higher level writing assignments. We based both higher and lower level writing assignments on the same concepts drawn from chapters of the accompanying textbook but which dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Bloom's Taxonomy is also recommended to be included in the ESL writing courses due to its effectiveness in expanding students' ability to produce creative writing (Sham, 2016). This finding also concurs with Nevid et al (2017) findings whereby the researchers concluded that writing tasks should be designed and assigned with the use of Bloom Taxonomy as it helps the students foster writing skills and cognitive skills simultaneously.…”
Section: Theoretical Framework Of the Studysupporting
confidence: 89%
“…Bloom's Taxonomy is also recommended to be included in the ESL writing courses due to its effectiveness in expanding students' ability to produce creative writing (Sham, 2016). This finding also concurs with Nevid et al (2017) findings whereby the researchers concluded that writing tasks should be designed and assigned with the use of Bloom Taxonomy as it helps the students foster writing skills and cognitive skills simultaneously.…”
Section: Theoretical Framework Of the Studysupporting
confidence: 89%
“…Students identified key concepts and elaborated on them by relating them to class themes through questions such as, “How does this concept relate to theme x?” This technique required students to go beyond definitions or recognition of a concept and to delve into deeper levels of processing. Similarly, higher level writing assignments that require students to apply concepts have been shown to increase exam scores beyond those that focus on definitions and descriptions (Nevid, Ambrose, & Pyun, 2017). The deeper level of processing required to apply concepts results in better acquisition and retention.…”
Section: Discussionmentioning
confidence: 99%
“…The current study supports this body of research. Perhaps if participants in the current study had been required to complete WTL assignments for each chapter (instead of just 5 of the 13), as was done in Nevid, Ambrose, and Pyun’s (2017) study, participants would have acquired and retained more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To secure the validity of the selection procedure (see below), the three authors discussed the selection of studies proposed by the first author and decided on the basis of consensus whether studies should be included and for which of the discriminated types of instruction they were representative. An example is Nevid et al (2017) using elaborated writing assignments. The question was whether the writing assignments also included some type of instruction directed at writing-to-learn.…”
Section: Procedures For Search and Selection Of Literaturementioning
confidence: 99%